EFFECT OF GREEN SPACES ON MENTAL HEALTH; THE RELATIONSHIP BETWEEN NATURAL ENVIRONMENT AND DEPRESSION - ÖZÇALIK, Mahire; Alabed, Dr. Abed; ORHUN, Nimetcan Mehmet (Malaysian Journal of Public Health Medicine, 2025)
Green spaces are well-recognized for their socio-economic and environmental benefits in urban areas, contributing to both an enhanced natural environment and improved human health.The aim of this study is to examine the effects of green areas on depression among adults in Türkey. A cross-sectional study was carried out among adults using a questionnaire distributed via Google Forms for data collection.The questionnaire was divided into three parts. The first part gathered socio-demographic information. The second part assessed participants' perceptions of the natural landscape architecture of their environment. The third part measured depression levels using the Beck Depression Inventory, utilizing its Turkish version. A total of 311 people participated in the study. Two thirds of the participants were female (65.6%), half of them were married (49.8%), more participants age between 21–30 years old (41.2%) and majority (79.9%) of them live in urban area. The depression levels of the individuals were statistically significant according to their age (p = 0.001), the proximity to the nature of the place where they live (p=0.027), spending time in natüre (p=0.014) and participants who achieved their goals (p=0.033). The study found that depression levels were significantly lower among individuals who lived near nature, spent time in green spaces, and felt they had achieved their goals. These results suggest that access to natural environments may support better mental health and should be considered in urban public health planning.